Tyrrell, Allan (London, 2011)
2011 "Tyrrell, Allan", 2011, HistoryTalk Allan was a wood machinist, a skilled worker. He talks about his apprenticeship in the 1960s. He worked for various companies including Rolls Royce, Harrods and the Royal Navy Docks.